1996
DOI: 10.1021/bi9521147
|View full text |Cite
|
Sign up to set email alerts
|

pH Dependencies of the Tetrahymena Ribozyme Reveal an Unconventional Origin of an Apparent pKa

Abstract: The L-21 ScaI ribozyme derived from the Tetrahymena thermophila pre-rRNA group I intron catalyzes a site-specific endonucleolytic cleavage of RNA, DNA, and chimeric RNA/DNA oligonucleotides: CCCUCUA5 + G-->CCCUCU + GA5. The pH-rate dependence was determined for the reaction of the E.G complex with the oligonucleotide substrate d(CCCUC)r(U)d(A5) [(kcat/Km)S conditions]. Although it was shown that the pH dependence is not affected by specific buffers, there is inhibition by specific monovalent cations. The intri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
85
0

Year Published

1996
1996
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(94 citation statements)
references
References 36 publications
9
85
0
Order By: Relevance
“…S and P with a 2′-deoxyribose substitution at position -1 were used to ensure that the chemical step was rate-limiting (57). This conclusion was confirmed by the observation of a log-linear pH dependence between pH 6.2 and 8.1 (data not shown, (5,59,60)). …”
Section: Measurement Of the Rate Constant For The Chemical Step And Tsupporting
confidence: 59%
“…S and P with a 2′-deoxyribose substitution at position -1 were used to ensure that the chemical step was rate-limiting (57). This conclusion was confirmed by the observation of a log-linear pH dependence between pH 6.2 and 8.1 (data not shown, (5,59,60)). …”
Section: Measurement Of the Rate Constant For The Chemical Step And Tsupporting
confidence: 59%
“…Herschlag and coworkers (20) have pointed out that an apparent pK a can result from deprotonation of multiple functional groups each with a pK a significantly greater than the apparent pK a . We attempted to fit the RG data in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Previous work with E ScaI showed that the chemical step is pH-dependent, increasing in a log-linear fashion from pH ∼5-9 for -1d,rS (Herschlag & Khosla, 1994;Knitt & Herschlag, 1996). For the G414-containing ribozyme, the rate constant for approach to the internal equilibrium (k obs ) k f + k r ; Scheme 1) was also log-FIGURE 4: Regeneration of S* provides evidence for the establishment of the internal equilibrium (K int ).…”
Section: Observation Of An Internal Equilibrium For the L-21g414 Ribomentioning
confidence: 90%